Petrology, geochemistry and tectonic setting of alkaline mafic rocks in the Jalal Abad area in the NW of Zarand (Kerman Province): Evidence for Paleo-Tethys rifting in the Central Iran - Yusef Vesali; Darush Esmaeili; Fatemeh Sepidbar; Maryam Sheibi; Shojaaldin Niroomand (پترولوژی, 2018)
The Jalal Abad region lies within the southern sector of Posht Badam block near to Jalal Abad, Najaf Abad iron deposits. In this region, several mafic intrusions and associated dyke and sills were intruded within the volcano-sedimentary unit of Rizu series and magnetite veins producing a narrow contact metamorphic aureole and overlain by Desu Series dolomites. These intrusion massives include irregular coarse- grained gabbro- diorites stocks and several NW-SE-trending basaltic dykes and sills. Petrographical and geochemical studies on the Jalal Abad mafic units reveal that they are alkaline in nature and based on the tectonic discrimination diagrams are grouped in alkaline basalts field of the intra-continental rift setting. They display LREE enrichment and HREE depletion, and significant enrichment in LILE in comparison to HFSE and HREE. Compositionally, they resemble modern OIB and the Hawaiian alkaline basalts. Magmas of these OIB-type and alkaline rock associations formed from partial melting of garnet- lherzolite facieses in the plume source, during the rift-drift and seafloor spreading evolution of the Proto-Tethys oceanic lithosphere during the Ordovician through Silurian periods.